Answer:
[tex]m = 3b+6[/tex]
Step-by-step explanation:
Given
[tex]f(x)=3x^2 - 9[/tex]
Required
The average rate over [tex][2,b][/tex]
Average rate (m) is calculated using:
[tex]m = \frac{f(b) - f(a)}{b - a}[/tex]
Where
[tex][a,b] = [2,b][/tex]
So, we have:
[tex]m = \frac{f(b) - f(2)}{b - 2}[/tex]
Calculate f(b) and f(2)
[tex]f(x)=3x^2 - 9[/tex]
[tex]f(b)=3b^2 - 9[/tex]
[tex]f(2)=3*2^2 - 9 = 12 - 9 = 3[/tex]
So, we have:
[tex]m = \frac{f(b) - f(2)}{b - 2}[/tex]
[tex]m = \frac{3b^2 - 9 - 3}{b - 2}[/tex]
[tex]m = \frac{3b^2 - 12}{b - 2}[/tex]
Expand the numerator
[tex]m = \frac{3b^2 + 6b-6b-12}{b - 2}[/tex]
Factorize
[tex]m = \frac{b(3b + 6)-2(3b+6)}{b - 2}[/tex]
Factor out 3b + 6
[tex]m = \frac{(b -2)(3b+6)}{b - 2}[/tex]
Cancel out b - 2
[tex]m = 3b+6[/tex]